Implementation of Education Financing Management in Improving the Quality of Learning in Junior High Schools - Husnidar, Husnidar; Khairuddin, Khairuddin; Bahrun, Bahrun (Journal of Educational Management and Learning, 2024)
This study investigates the implementation of education financing management in improving the quality of learning at SMP Negeri Unggul Tunas Nusa and SMP Negeri 1 Susoh in Aceh Barat Daya Regency, Indonesia. The research focuses on education financing management's planning, implementation, supervision, and accountability. A qualitative approach was employed, involving interviews, observations, and document analysis. The findings reveal that planning education financing at both schools follows the guidelines set by the Ministry of Education, Culture, Research, and Technology of Indonesia and is formulated in the annual School Activity and Budget Plan (RKAS). The implementation of education financing adheres to the principles of flexibility, effectiveness, efficiency, transparency, and accountability, with the use of BOS funds directed towards supporting the learning process and improving the quality of education. Internal and external parties supervise education financing to ensure funds' accountable, transparent, effective, and efficient utilization. The implementation of transparency and accountability in education financing management has been running very well, with regular reports and budget accountability meetings involving various stakeholders. The study concludes that the implementation of education financing management at SMP Negeri Unggul Tunas Nusa and SMP Negeri 1 Susoh has been carried out effectively, efficiently, transparently, and accountably, contributing to the improvement of learning quality. Further research is recommended to explore the implementation of education financing management in other schools or regions to gain a more comprehensive understanding of the practices and challenges in improving the quality of learning through effective education financing management.